Meningkatkan Prestasi Non Akademik Melalui Manajemen Kegiatan Ekstrakurikuler - Supriadi; Rokhman, Mauhibur; Nur Kholis, Mohammad Maulana (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
This research examines the implementation of extracurricular activities aimed at improving students' non-academic achievements at Tabanan Islamic Elementary School. A qualitative approach was employed, utilizing observation, interviews, and documentation study methods. The research findings indicate that Tabanan Islamic Elementary School executes extracurricular activities with a focus on key management stages, including planning, organizing, implementing, and evaluating. During the planning stage, coordination meetings are convened to identify student interests and develop work programs, ensuring alignment with both student interests and school objectives. Organizing entails involving various stakeholders with clearly defined roles and responsibilities. The implementation phase encompasses continuous preparation, regular practice, and program execution, with supervisors playing a crucial role in guiding students. Evaluation is conducted through annual meetings to pinpoint program deficiencies for improvement. The successful implementation is facilitated by competent human resources, adequate infrastructure, a diverse array of sports, science, and technology, arts and culture activities aimed at nurturing students' talents, fostering character development, and motivational support provided by coaches. Overall, the implementation of extracurricular activities at Tabanan Islamic Elementary School adheres to sound management principles and is bolstered by various factors aimed at enhancing students' non-academic achievements through high-quality activities fostering talent, interest, and character development.